MODERN VIEW ON THE STRUCTURE OF THE VASCULAR EXTRACELLULAR MATRIXS - Tanaskovic Stankovic, Sanja Lj (Medicinski časopis, 2014)
Endothelium, smooth muscle cells and connective tissue arethree basic structural components of the blood vessel wall. They are all finely interconnected and form one active, highly integrated organ. The majority of the connective tissue is located in the subendothelial layer of the tunica intima, but also is abundant in the tunica adventitia. Connective tissue is composed primarily of two elements: cells and a matrix which, in turn, is built from ground substance and fibers. Ground substance is a amorphous and viscous fluid containingglycosaminoglycans, proteoglycans and structural glycoproteins that are aranged in a complex manner. Fibers, on the other hand, are main supportive elements in the connective tissue mainly responsible for its hardness and elasticity. There are three types of protein fibers found within the matrix. Collagen and reticular fibers are built from protein collagen while elastic fibers are composed of protein elastin. Structure and composition of the extracellular matrix plays a crucial role in preservation of the structural and functional characteristics of the blood vessel wall. Keywords: blood vessel wall, connective tissue, extracellular matrix